The usage of CO2 tracer gas methods for ventilation performance evaluation in apartment buildings - Mikola, Alo; Kõiv, Teet-Andrus; Rehand, Juhan; Voll, Hendrik (International Conference “Environmental Engineering”, 2017)
The purpose of the study is to investigate the potential of the CO2-based tracer gas methods for the ventilation performance evaluation in apartment buildings. To test and elaborate the methods, the ventilation air change rate (ACR) and air change efficiency (ACE) measurements were performed. The methods were tested in laboratory conditions and apartments with natural ventilation, room-based ventilation units, exhaust ventilation and mechanical exhaust ventilation with fresh air radiators. Concentration decay method is applied with both artificially and naturally increasing the concentration of tracer gas. The ACR is also calculated using metabolic constant dosing method with the effective volume. As the traditional tracer gas methods give the correct result only in case of perfect mixed ventilation, then the ACE is also measured. To observe the effectiveness of the air change and the level of air mixing multiple CO2 sensors placed in different positions. The tracer gas measurements were carried out in naturally ventilated apartments to study the influence of the inner doors to the ACE. The daily variation of CO2 level in case the long-term CO2 measurements gives us the possibility to calculate the ACR when inhabitants are sleeping or have left the apartment. Using the CO2 as the natural tracer gas and the concentration decay method together with the metabolic constant dosing strategy, we can calculate the CO2 concentrations according to the long-term CO2 measurements without knowing the exact emission of inhabitants. The studied methods are inexpensive and at the same time sufficiently accurate for airflow measurements. Another reason for the study comes from the ventilation retrofit process in Estonia where the single room ventilation units are used. As these wall-mounted ventilation units are sensitive to in- and outside pressure differences the measurement of ventilation airflow in the traditional way can be inaccurate.